2014
DOI: 10.1063/1.4897912
|View full text |Cite
|
Sign up to set email alerts
|

A dynamical systems analysis of the data assimilation linked ecosystem carbon (DALEC) models

Abstract: Changes in our climate and environment make it ever more important to understand the processes involved in Earth systems, such as the carbon cycle. There are many models that attempt to describe and predict the behaviour of carbon stocks and stores but, despite their complexity, significant uncertainties remain. We consider the qualitative behaviour of one of the simplest carbon cycle models, the Data Assimilation Linked Ecosystem Carbon (DALEC) model, which is a simple vegetation model of processes involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…DALEC considers a labile pool in vegetation, which is replenished by carbon from leaves before senescence and fuels the leaf production in the next spring. The labile pool is largely decoupled from forest biomass dynamics [ Chuter , ].…”
Section: Methodsmentioning
confidence: 99%
“…DALEC considers a labile pool in vegetation, which is replenished by carbon from leaves before senescence and fuels the leaf production in the next spring. The labile pool is largely decoupled from forest biomass dynamics [ Chuter , ].…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Chuter et al (2015) for the previous DALEC evergreen and deciduous models, the evolution of the carbon pools for DALECv2 show a tipping point which depends on the parameters 490 p 1 to p 17 . Given a set of parameters p the fast carbon pools C lab , C f , C r and C l grow or decay rapidly to an equilibrium state.…”
mentioning
confidence: 57%
“…The work of Williams et al (2005) established the benefit of using DALEC together with net ecosystem exchange (NEE) of CO 2 measurements in a Bayesian framework to estimate initial carbon stocks and model parameters, to improve flux predictions for ecosystem models and to quantify uncertainties. Inter-comparison experiments (Fox et al, 2009;Hill et al, 2012) have then demonstrated the relative merit of various inverse modelling strategies using NEE and MODIS leaf area index observations: most results agreed on the fact that parameters and initial stocks directly related to fast processes were best estimated with narrow confidence intervals, whereas those related to slow processes were poorly estimated with very large uncertainties. Other studies have tried to overcome this difficulty by adding complementary data streams (see Richardson et al (2010)) or by considering longer observation windows (see Hill et al (2012)).…”
Section: Introductionmentioning
confidence: 80%